Utilizing Mobile Application for Learning English Speaking Skills in IDLE Context: - Nadiva, Umi; Sundari, Hanna; Muhajir, Achmad (JADEs Journal of Academia in English Education, 2024)
This paper has the purpose of reporting students’ perceptions of the utilization of a mobile application for learning English speaking skills, Cakap Application, particularly in informal digital learning environment. To examine students’ perceptions, a qualitative technique was applied using a descriptive research design. The participants are from different high school students as well as the users of Cakap application. The information was obtained by a semi-structured interview with the questions grounded by the concepts of Speaking, IDLE, and TAM. After analyzing the data with thematic procedure analysis, it was revealed the generated themes: utilization and the benefits of the mobile application, Cakap, in improving speaking skills. The participants expressed that this application has simple access and provides feedback from the mentor expert that leads to benefits in speaking skills. This application also gives a pronunciation model and vocabulary building that benefit the improvement of speaking skills